Sosialisasi dan Pelatihan Pembuatan Pangan Sehat Lokal Berbasis Kelor Untuk Peningkatan Gizi Balita, Ibu Hamil Dan Menyusui di Desa Gerimax Indah, Kec. Narmada, Kab. Lombok Barat - Satrijo Saloko; I Wayan Sweca Yasa; Dody Handito; Lalu Unsunnidhal; Lingga Gita Dwikasari (Universitas Mataram, 2023)
stunting and malnutrition in Indonesia. The prevalence of stunting in NTB reaches 37.20% (Dikes NTB, 2017), NTB has special stunting areas, one of which is Gerimax Indah Village, Narmada, West Lombok. Many children are malnourished, and pregnant and breastfeeding mothers experience deficits in energy and protein intake. On the other hand, the resource potential and productivity of local food that can be used as nutritional intake, such as corn, cassava and moringa in NTB, continues to increase, and this indicates that these local food products have great potential as alternative food sources of nutrition. Moringa leaves as a source of protein and antioxidants are very good for people with malnutrition. To save time and make serving easier, it is necessary to prepare local moringa-based food products that are easy to serve in instant form and have high nutritional content. To save time and make serving easier, it is necessary to prepare local moringa-based food products that are easy to serve in instant form and have high nutritional content. To answer this challenge, the team has carried out activities by making processed food made from Moringa leaves in the form of Moringa leaf pukis for children, pregnant women and breastfeeding mothers. Therefore, it is necessary to carry out socialization and training on making local healthy food based on Moringa to improve the nutrition of toddlers, pregnant and breastfeeding women in Gerimax Indah Village, Kec. Narmada, Kab. West Lombok. The method that will be used in implementing this service is to apply the socialization and training method for making local healthy food based on moringa. The output must be in the form of articles in nationally accredited journals and publications in the mass media, apart from that, there are also additional outputs in the form of statements about the use of research results by partners or the public